Optimalisasi Penggunaan Variasi Filter Pada Pesawat Sinar-X Mobile Guna Mencapai Nilai Entrance Skin Exposure (Ese) Sesuai Organ Pemeriksaan - Oki Dewi Pamungkas; Utari Utari; Suharyana Suharyana; Riyatun Riyatun; Nining Hargiani (Universitas Sebelas Maret, 2020)
Abstract: This study was to determine the effect of variations in the type and thickness of the filter on the ESE and HVL values. The use of filters aims to eliminate low energy X-rays, increase effective energy, and reduce dose acceptance to patients. This variation of Al with Cu and Al with Zn filters uses a voltage (70, 80, and 90) kV, 20 mAs, 100 cm SSD, and an irradiation field area of 10 cm x 10 cm. The result of measuring the consistency of the X-ray tube voltage has the largest error value of 4.93%. At a voltage of 90 kV, the measurement results of the variation of Al filter with Cu thickness of 0.2 mm and 0.3 mm and Al filter with Zn thickness of 0.25 mm and 0.50 mm are within the tolerance limits of the thorax examination organ. While the measurement results of the Al filter variants with a Cu thickness of 0.4 mm and an Al filter with a Zn thickness of 0.75 mm are within the tolerance limit of the cranium examination organ. The ESE half value can use 3.03 mm Al, equivalent to 0.135 mm Cu or 0.22 mm Zn.Abstrak: Penelitian ini untuk mengetahui pengaruh variasi jenis dan ketebalan filter terhadap nilai ESE dan HVL. Penggunaan filter bertujuan untuk mengeliminasi sinar-X energi rendah, meningkatkan energi efektif, dan mengurangi penerimaan dosis pada pasien. Variasi filter Al dengan Cu dan Al dengan Zn ini menggunakan tegangan (70, 80, dan 90) kV, 20 mAs, SSD 100 cm, dan luas lapangan penyinaran 10 cm x 10 cm. Hasil pengukuran konsistensi tegangan tabung sinar-X memiliki nilai error terbesar 4,93%. Pada tegangan 90 kV hasil pengukuran variasi filter Al dengan Cu ketebalan 0,2 mm dan 0,3 mm dan filter Al dengan Zn ketebalan 0,25 mm dan 0,50 mm dalam batas toleransi organ pemeriksaan thorax. Sedangkan hasil pengukuran varisi filter Al dengan Cu ketebalan 0,4 mm dan filter Al dengan Zn ketebalan 0,75 mm dalam batas toleransi organ pemeriksaan cranium. Nilai setengah ESE dapat menggunakan 3,03 mm Al, setara dengan 0,135 mm Cu atau 0,22 mm Zn.